Large Multicentric Synchronous Extra-Abdominal Fibromatosis of the Leg and Foot: A Case Report - Ashwini M. Bakde; Vignesh Gunasekaran; Aarti Anand; Nisha Meshram (Indian Journal of Radiology and Imaging, 2024)
Extra-abdominal fibromatosis is an uncommon, benign locally aggressive fibrous soft-tissue tumor that usually occurs in the shoulders, chest wall, back, thigh, and head and neck affecting the young adult population. It is commonly located in the subcutaneous tissue and may infiltrate the adjacent skeletal muscles. We hereby report a rare case of a large extra-abdominal fibromatosis of the leg and foot in a 38-year-old woman. The patient presented with a large voluminous lesion clinically and on imaging, which was difficult to diagnose. Magnetic resonance imaging (MRI) was very helpful in diagnosing the lesion. It revealed a large relatively well-defined, lobulated hypointense mass in the posterior compartment of the leg with extension into the lower thigh and foot with local infiltration into the gastrocnemius and soleus muscles. An incisional biopsy was performed, and the mass was diagnosed on pathological examination as a spindle-shaped fibroblast proliferation suggesting extra-abdominal fibromatosis.